Der Beitrag der Werkstoffforscher: Interview mit Manfred K. Semlitsch und Claude B. Rieker (Maurice E. Müller und die Entwicklung künstlicher Hüftgelenke in der Schweiz. Zeitzeugenbefragungen zur Geschichte einer Medizintechnik, 2023)
Manfred K. Semlitsch, a chemist with a doctorate from Graz in Austria, joined Gebrüder Sulzer AG in Winterthur in 1966 and researched and developed materials for hip prostheses from 1967 to 1996. Semlitsch became involved in prosthetics in 1967 after Hans-Georg Willert, who later became a professor of orthopaedics in Göttingen, approached Sulzer with histopathological problems that had arisen with the first prostheses manufactured by the precision foundry for Arnold Huggler and implanted at the Balgrist Orthopaedic University Clinic in Zurich in 1961/62. The collaboration with Willert led to around thirty years of research into biomaterials for hip joint prostheses. From 1970, Semlitsch headed the research and development group for implant materials in the newly created Medical Technology Product Division of Sulzer Brothers Ltd. Claude B. Rieker, who holds a doctorate in materials science, is Director of Scientific Affairs at Zimmer Biomet GmbH in Zug and Winterthur. He joined Protek AG in 1990 as a development engineer. Over the next three decades, he held various positions during the integration of Protek AG into the gradually independent Sulzer Medica AG, then the complete separation from the Sulzer Group in 2001 and the takeover of the company, now operating under the name Centerpulse, by the then Zimmer Holding in 2003 and finally the acquisition of its competitor Biomet by Zimmer in 2015. Rieker was Head of Product Management at Protek from 1992 and Head of Hip Development from 1995, Director of Tribology at Sulzer Medica, Centerpulse and Zimmer from 1996 and Director of European External Research at Zimmer in 2005 and 2006.